Combining transcranial direct current stimulation and computerized cognitive training for post-stroke cognitive recovery: Study protocol for a randomized controlled trial with optimized temporal intervention sequences - Xinling Wei; Jianwei Xia; Rui Luo; Peng Hu; Yuanyuan Wu; Jia Liu; Luping Song; Naifu Jiang; Minghong Sui (PLoS ONE, 2026)
Background Post-stroke cognitive impairment is a common and severe complication of stroke, significantly affecting patients’ daily life and rehabilitation. Although transcranial direct current stimulation combined with computerized cognitive training has shown potential for improvement, current studies still have key limitations. Most have used only simultaneous intervention protocols, without systematically comparing sequential combination strategies, making it difficult to determine the optimal clinical approach. Objectives The core objective of this study will be to address the existing research gap by comparing sequential intervention strategies and to resolve the key issue of identifying the optimal clinical approach. Methods This study will use a single-center, double-blind, randomized controlled trial design. A total of 60 patients with post-stroke cognitive impairment will be randomly assigned in a 1:1:1:1 ratio to four groups: three intervention groups receiving computerized cognitive training combined with transcranial direct current stimulation at different timings (pre-training, concurrent, or post-training), and one sham control group. All interventions will be administered five times a week for two consecutive weeks. Follow-up assessments will be conducted at 4 and 12 weeks post-intervention. Discussion This trial will systematically evaluate the optimal timing strategies for combining tDCS and CCT in PSCI. The hypothesized mechanisms are: (1) synchronous stimulation enhancing cognitive processing efficiency through immediate synaptic changes, (2) pre-training stimulation promoting plasticity via long-term potentiation-like modifications, and (3) post-training stimulation consolidating training effects by modulating neuronal synchrony. High-sensitivity cerebral oxygenation parameters will be used to assess microcirculatory improvements, linking physiological changes to cognitive recovery. However, ceiling effects and test biases will potentially limit the accuracy of long-term results, while sample size and lack of stratification based on brain lesion characteristics may introduce heterogeneity. Future studies will need to incorporate multimodal neuroimaging for stratified analysis and should develop personalized interventions based on lesion severity, disease stage, and timing to address therapeutic challenges and advance precision rehabilitation. Trial registration: ChiCTR2500102565.[Chinese Clinical Trial Registry (ChiCTR), https://www.chictr.org.cn/ ] [Registered on May 16, 2025]